Multi-Omics Approach in Amelioration of Food Products - Bandita Dutta; Dibyajit Lahiri; Moupriya Nag; Rose Abukhader; Tanmay Sarkar; Siddhartha Pati; Siddhartha Pati; Vijay Upadhye; Soumya Pandit; Mohamad Faiz Mohd Amin; Abdel Rahman Mohammad Said Al Tawaha; Manoj Kumar; et al. (Frontiers in Microbiology, 2022)
Determination of the quality of food products is an essential key factor needed for safe-guarding the quality of food for the interest of the consumers, along with the nutritional and sensory improvements that are necessary for delivering better quality products. Bacteriocins are a group of ribosomally synthesized antimicrobial peptides that help in maintaining the quality of food. The implementation of multi-omics approach has been important for the overall enhancement of the quality of the food. This review uses various recent technologies like proteomics, transcriptomics, and metabolomics for the overall enhancement of the quality of food products. The matrix associated with the food products requires the use of sophisticated technologies that help in the extraction of a large amount of information necessary for the amelioration of the food products. This review would provide a wholesome view of how various recent technologies can be used for improving the quality food products and for enhancing their shelf-life.